Russia in the process of constructing regional structures in Southeast Asia - Pietrasiak, Małgorzata (Eastern Review, 2021)
The article aims to show the integration processes in Southeast Asia, with regard to the participation of Russia, and to determine the reason why Russia takes part in them. Based on the demonstration of the international process, two theses have been proven: (1) The project of establishing a Greater Eurasia with the participation of the Eurasian Economic Union (EAEU), the Shanghai Cooperation Organisation (SCO) and ASEAN is a grandiose and strategic goal for Russia. The project is supposed to recall the traditional policy conducted by Russia, consisting of it playing the role of a bridge between Asia and Europe drawing China’s attention to this alternative proposal to the Chinese concept of the Belt and Road Initiative. (2) Russia is a player in the geopolitical game in Southeast Asia, even though it is perceived as the closest ally of China. Under the circumstances, where the relations with the EU have been destabilised, it is in the interest of Russia to further the integration and stabilisation of the region with its more active participation. Russia’s more active participation in regional integration is hampered by its low level of economic cooperation with countries in the region and its image: the activities of Russia are still perceived through the prism of the actions and interests of China, its strategic ally both on a regional as well as global scale.